Lunar climbing adventure consultant: enhancing climbers' professionalism, well-being and fitness - Ahmad Dahlan, Abdul Rahman; Junaidi, Nurul Syafikah; Abd Jamil, Nur Ameela Najwa; Abdul Ghariff, Ahmad Syhir (Eclat Research Publication, 2017)
This paper proposed a one-stop service platform focus on booking for guiding and coaching, online consulting regarding fitness and wellness of climbers, trip and event organisers and provide certificate from the South East Asia Climbing Federation named Lunar Climbing (LCAC). This system has the ability to book a climbing session based on package options provided. The system provides a platform for advertising trips or events where the organisers need to sign-up as members based on terms and conditions.